Genome-wide identification of miRNAs and targets associated with cell wall biosynthesis: Differential roles of dlo-miR397a and dlo-miR408-3p during early somatic embryogenesis in longan. (October 2022) - Xu, Xiao Ping; Cao, Qing Ying; Guan, Qing Xu; Mohammadi, Mohammad Aqa; Di Cai, Rou; Chen, Xiao Hui; Zhang, Zi Hao; Chen, Yu Kun; Xuhan, Xu; Lin, Yu Ling; Lai, Zhong Xiong
Abstract: The dynamic alterations in cell wall (CW) biosynthesis play an essential role in physiological isolation during the plant somatic embryogenesis (SE). However, the mechanisms underlying the functions of cell wall-associated miRNAs (CW-miRNA) remain poorly understood in plant SE. Here, we have identified 36 distinct candidate miRNAs associated with CW biosynthesis from longan third-generation genome as well as miRNA transcriptome, and modified RLM-RACE validated four distinct miRNA, which specifically targeted four CW-related genes. More importantly, we found that the dlo-miR397a-antagomir significantly enhanced DlLAC7 expression and improved laccase activity. Interestingly, inhibition of dlo-miR397a increased CW lignin deposition and promoted the tightening of protodermal cell by miRNA-mimic technology during early SE. Moreover, overexpression of dlo-miR408–3p (dlo-miR408–3p-agomir) markedly decreased DlLAC12 expression. dlo-miR408–3p-agomir activated rapid cell division, thus promoting the globular embryo (GE) development, which might be due to high DNA synthesis activity in protoepidermal cells, rather than affecting lignin synthesis. The subcellular location also indicated that both DlLAC7 and DlLAC12 proteins were primarily localized in CW and regulated CW biosynthesis. Overall, our findings provided new insight on the molecular regulatory networks comprising various miRNAs associated with cell wall, and established that dlo-miR397a and dlo-miR408–3p played differential roles during early SE in longan. The findings also shed some light on the potential role of miRNA target DlLAC regulating in vivo embryonic development of plant. Highlights: 36 miRNAs associated with cell wall(CW) biosynthesis were identified, four of them cleaved four cell wall-related genes in longan early somatic embryogenesis (SE). dlo-miR397a-antagomir substantially enhanced DlLAC7 expression and laccase enzyme activity,  promoting the tightening of protodermal cell in globular embryo (GE). dlo-miR408-3p-agomir activated rapid cell division and stimulated GE development, rather than modulating lignin synthesis by targeting DlLAC12.